Early Field Recordings: A Catalogue of Cylinder Collections at the Indiana University Archives of Traditional Music, edited by Anthony Seeger and Louise S. Spear. Indiana University Press, Bloomington, 1987. xviii plus 198 pp. (Reprinted from Journal of Contemporary African Studies Vol.7 No. 1/21988 by permission) - Tracey, Andrew (International Library of African Music, 2017)
pages: 110-111
Keywords: African Music